Sustainable Forest Management Practices in Tropical Asia: A Review - Ming Kiri; Vicheka Rith; Chak Sothy (Yayasan Adra Karima Hubbi, 2024)
Tropical Asia is home to some of the world's most diverse and ecologically significant forests. However, these forests face immense pressures from deforestation, climate change, and unsustainable logging practices. Sustainable forest management (SFM) has emerged as a vital approach to balance ecological health, economic viability, and social equity in forest use. This review aims to evaluate current sustainable forest management practices in tropical Asia, identifying effective strategies and challenges faced in implementation. The objective is to provide insights into how SFM can enhance forest conservation while supporting local communities. A comprehensive literature review was conducted, analyzing peer-reviewed articles, policy documents, and case studies related to SFM in tropical Asia. Key themes were identified, including community participation, adaptive management, and certification schemes, with a focus on their effectiveness and applicability. The findings indicate that successful SFM practices often incorporate community involvement and traditional ecological knowledge. Certification systems, such as the Forest Stewardship Council (FSC), have proven effective in promoting sustainable practices among local and commercial stakeholders. However, challenges such as inadequate policy frameworks and lack of financial resources hinder broader implementation. This review concludes that sustainable forest management practices in tropical Asia are essential for biodiversity conservation and community resilience. Enhancing stakeholder collaboration and strengthening policy frameworks are crucial for overcoming existing challenges. Future efforts should focus on integrating local knowledge and adaptive management strategies to ensure the long-term sustainability of forest resources.